THE ATHENIAN ALTAR AND THE AMAZONIAN CHATBOT: A PAULINE READING OF ARTIFICIAL INTELLIGENCE AND APOCALYPTIC ENDS: with Robert M. Geraci and Simon Robinson, "Introduction to the Symposium on Artificial Intelligence and Apocalypticism"; Beth Singler, "Existential Hope and Existential Despair in AI Apocalypticism and Transhumanism"; Michael Morelli, "The Athenian Altar and the Amazonian Chatbot: A Pauline Reading of Artificial Intelligence and Apocalyptic Ends"; Victoria Lorrimar, "Mind Uploading and Embodied Cognition: A Theological Response"; and Syed Mustafa Ali, "'White Crisis' and/as 'Existential Risk, ' or the Entangled Apocalypticism of Artificial Intelligence.". Issue 1 (17th February 2019) - Morelli, Michael
Abstract: This article explores questions about chatbots in particular and artificial intelligence (AI) in general from a Pauline, that is, a Christian theological perspective. It does so in a way that focuses on a particular scene in the New Testament: Paul in the Athenian Areopagus, considering an altar to an "unknown God, " quoting Greek poets and philosophers, and sharing curious theology as he dialogues with Stoic and Epicurean thinkers (Acts 17:16–34). By examining the sociohistorical nuances of this scene and their philosophical and theological implications, this article shows how the altar Paul considers philosophically and theologically becomes the focal point for an important dialogue about apocalyptic ends, or ideas about who we are, where we are going, and who or what is responsible for that who‐ness and where‐ness. In turn, this can teach us how to ask practical questions, which can uncover the unsuspected apocalyptic ends represented by, or even contained within, common technological objects such as chatbots.